Mucosa-associated lymphoid tissue lymphoma of parotid gland with involvement of subglottis and trachea - Natsumi Uehara (Acta Oto-Laryngologica Case Reports, 2018)
Although it is well recognized that the salivary glands may acquire Mucosa-associated lymphoid tissue (MALT) lymphoma as a result of Sjögren syndrome (SS), involvements of subglottis and trachea are rare. A 78-year-old woman was referred to our hospital for an enlarged mass of the right parotid area with a history of SS for 7 months. Two weeks after the first visit, she presented with the complaint of stridor and difficulty in breathing. Laryngoscopy revealed the stricture of subglottic space due to the nodular submucosal mass. She was emergently admitted and underwent tracheostomy. Biopsies of the tracheal mucosa and subglottic nodular submucosal mass were pathologically diagnosed as MALT lymphoma. After 6 courses of rituximab plus CHOP (R-CHOP), all lesions disappeared and tracheal stoma were successfully closed. Although MALT lymphoma of upper respiratory tract is extremely rare, respiratory tract should be examined in the patients of parotid lymphoma associated with SS.